Estudo sobre a adesão da Escherichia coli enteropatogênica atípica O26:H11 a células epiteliais - Dulguer, Michelle Vanzella [UNIFESP] (2006)
The O26 serogroup of enteropathogenic Escherichia coli (EPEC) is one of the most frequently implicated in infant diarrhea and is also common among enterohemorrhagic E. coli (EHEC) strains. The most common O26 strains belong to EPEC/EHEC serotype O26:H11. In a previous report, atypical EPEC strains O26:H11 isolated from children with diarrhea exhibited a localized adherence (LA) pattern within 3 hours, but do not harbor the BFP fimbriae correlated with the LA phenotype of typical EPEC. One isolate, E. coli 22 was used to characterize its genetic determinants. A genomic cosmid library of E. coli 22 was generated in E. coli K12 and the resulting clones were screened for LA adherence to HEp-2 cells. One cosmid clone, pV-B-6, exhibited adherence in a diffuse pattern over the entire epithelial cell rather than the LA microcolony formation seen with E. coli 22. Transposon mutagenesis was utilized to identify the region of cosmid pV-B-6 responsible for the adhesive phenotype. One isolate tested negative for adherence (pV-B-6-Tn) was chosen for further analysis. DNA sequencing of a subclone of pV-B-6 revealed an open reading frame, ldaH, whose predicted protein product shares 73% amino acid identity with that of the E. coli K88 fimbrial gene faeH. This region was named the locus for diffuse adherence (lda). The aim of this study was to characterize the adhesin encoded by the lda locus that is responsible for mediating diffuse adherence to HEp-2 cells. SDS-PAGE of whole-cell cell lysates from E. coli 22 and pV-B-6 showed a broad band with an apparent molecular mass of 25 kDa, which was absent in the pV-B-6-Tn extracts. The 25-KDa band was excised from the gel, and its N-terminal amino acid sequence determined. The sequence corresponds to the mature form of LdaG, the major structural subunit. The expression of LdaG is induced on MacConkey agar at 37o C. To provide further evidence that the LDA adhesin was responsible for the diffuse adherence seen on HEp-2 cells, we raised polyclonal rabbit antiserum against the major structural subunit LdaG. Imuno blot analysis 17 showed that the antiserum recognized the 25-kDa band present in wildtype E. coli 22 and pV-B-6, but not the pV-B-6-Tn mutant. Treatment of pV-B- 6 with the antiserum completed inhibited diffuse adherence of pV-B-6 to the HEp-2 cells. Immunogold labeling with LdaG antiserum identified an amorphous surface matrix with no obvious fimbrial structure. At higher magnification, very fine wiry fibrils forming mesh-like structures could be visualized. To determine whether the lda locus was specific to our O26:H11 strain or if it is present in other E. coli strains, we performed colony blots and HEp-2 adherence on a collection of 65 atypical EPEC strains representing 34 O serogroups. Most (61.5%) of strains were positive for HEp-2 localized-like adherence assay and all strains were ldaH probe negative. We also tested 13 atypical EPEC strains, which belonged to Dr. Luiz R. Trabulsi and ldaH was found in four O26 LA positive strains. These strains were tested with an ldaG gene probe, but were negative. By using a K88 antiserum, it was possible to demonstrate different antigenic determinants, between LDA and K88 adhesins. A streptomycin-treated mouse model was used to compare the intestinal colonization capacity of E. coli 22 strain with that of its ∆ldaG derivative (LDA1). The results showed that E. coli 22 adheres and colonizes the cecum of C57BL/6J mice more efficiently than the LDA1. In conclusion, we were able to characterize the LDA adhesin responsible for diffuse adherence to HEp-2 cells. LDA is an afimbrial adhesin that contains a major subunit, LdaG, whose expression is induced on MacConkey agar at 37o C. Additional work is needed to characterize the role in virulence of the LDA adhesin.